PERBUATAN DAN TANGGUNGJAWAB HUKUM DALAM KONSEP USHUL FIQH - Muhammad Nur Ali (Istinbath : Jurnal Hukum, 2015)
The Existence of “ushul fiqh” which has been used by Muslims seem that there is stagnation in understanding and applying it. It is a must that“Usul fiqh” is applied in order it can be more flexible and contextual. In its development, there has been no methodology (manhaj) that can understand the “Shari'ah” completely and precisely, to overcome all the social problems that continue to evolve and change. Therefore, “ushul fiqh” is in effort to change a new paradigm, from textual to contextual although it raises many issues, especially the discourse of epistemology, methodology, and its implementation in society. An achievement of common good (al-masalhi al-ammah) community and apply “daruriyyah “dimension. An application of “ushul fiqh” in reality of Indonesian plural society is that “ijtihad li al-ijtima'iyyah” which is known as the process of extracting the laws against the problem of contemporary society by using a method and thinking of Muhammad ibn Idris ash-Syafi'i or from other thinking in the environment of “syafi’i madhab” in the priority scale and it is focus on achieving the common good, it is justice. The relevance between “ushul fiqh” action and social responsibility in the concept of Islamic law are: a) the study of “fiqh” and social reality which is strongly influenced by the public's willingness to apply the law of islam which are contextual and flexible with its socio-cultural; b) the substance about the conceptual framework Labor Women (TKW) needs a unification between the values ​​of Islam and justice which is proven in attitudes, behavior, utterance, actions, and thoughts.